2016
DOI: 10.3892/or.2016.4760
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 promotes endometrial cancer progress through epithelial-mesenchymal transition regulation

Abstract: Epithelial-mesenchymal transition (EMT) is a major cause of endometrial cancer (EC) to initiate invasion and metastasis. S100A4, a calcium-binding protein, is implicated in multistage of tumorigenesis and tumor progression. The correlation between S100A4 and EMT in EC is still unclear. This study was aimed to clarify the role of S100A4 in EC and the relationship between S100A4 expression and EMT markers. S100A4, E-cadherin, and vimentin were detected in tissues of EC patients (n=50) by immunohistochemistry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…It has been demonstrated that S100A4 can stimulate cancer cell migration and invasion by direct S100A4 and myosin-IIA interactions [106] or S100A4-induced MMPs secretion [107]. It has also been shown that S100A4 can induce EMT, promoting a mesenchymal, more-motile phenotype in cancer cells [108]. Lately, the ability of extracellular S100A4 to act on stromal cells and participate in tumor -stroma interactions has been addressed.…”
Section: S100a4a Tme Factormentioning
confidence: 99%
“…It has been demonstrated that S100A4 can stimulate cancer cell migration and invasion by direct S100A4 and myosin-IIA interactions [106] or S100A4-induced MMPs secretion [107]. It has also been shown that S100A4 can induce EMT, promoting a mesenchymal, more-motile phenotype in cancer cells [108]. Lately, the ability of extracellular S100A4 to act on stromal cells and participate in tumor -stroma interactions has been addressed.…”
Section: S100a4a Tme Factormentioning
confidence: 99%
“…Treatment with Janus kinase- and Signal transducer and activator of transcription 3-specific inhibitors, AD412 and STATTIC, respectively, significantly abrogated CAF-mediated cell proliferation, indicating the role of IL-6 activation in EC cell proliferation ( 27 ); also, aberrant S100A4 expression may predict EC progression and serve an important role in regulating EC cell invasion through EMT regulation. Therefore, S100A4 is a promising therapeutic target ( 28 ). In the present study, only four growth factors were studied; a more comprehensive analysis will be included in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth depends on interactions between multiple inter-dependent cell types, among these different cell types, CAFs are becoming a topic of study as recipients and as producers of pro-tumorigenic signals ( 29 ). There are a number of previous studies concerning the role of CAFs and their mechanisms of action in various tumors ( 27 , 28 , 30 , 31 ). Hwang et al ( 32 ) examined pancreatic cancer, and identified that cancer-associated stromal fibroblasts exhibited an important role in supporting and promoting growth and metastasis in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue specimens were obtained from patients who had been diagnosed with endometrial cancer (n = 50) and from normal endometria (n = 10) as previously described 29 . All patients had undergone surgical resections or biopsies at Wuhan Union Hospital between 2010 and 2013, and the diagnoses were confirmed by a gynaecologic pathologist.…”
Section: Methodsmentioning
confidence: 99%